EFL Students’ Experience in Speaking Practice through Muhadharah - Ika Yanti Ziska; Januarius Mujianto; Issy Yuliasry; Hendi Pratama (Universitas Negeri Semarang, 2023)
This research was conducted to obtain the influence of muhadharah as an extracurricular activity on students’ speaking ability. This study was qualitative research. The participants in the study consist of 15 eighth-grade students of junior high school (one of the private boarding schools in South Sulawesi). The researcher conducted interviews to obtain data from participants. The results of this study indicated that muhadharah is a good school extracurricular activity that can affect students’ speaking ability. The result of interviews shows that muhadharah as extracurricular activity significantly affects the students’ speaking ability in English. For example, in debriefing in speech procedures, increasing students’ vocabulary, learning how to make facial expressions or body gestures, and mentally training students to speak in front of the public. The interview result also shows deficiencies in extracurricular activities such as muhadharah. When the action is inappropriate because it is carried out at night, it takes students’ rest time and makes some students tired and sleepy. Some also said there are penalties if students are not joining muhadharah.